Effects of palm kernel meal level on live performance and gut morphology of broilers - Yaophakdee, Nisarat; Ruangpanit, Yuwares; Attamangkune, Seksom (Agriculture and Natural Resources, 2018)
A studywas conducted to determine the effects of feeding different levels of palmkernel meal (PKM) on the live performance and gut morphology of broilers. In total, 600 one-day-old broilers (Ross 308) were divided into two groups. Each group consisted of six replications with 50 birds (25 males and 25 females) each. The diets were: 1) corn-soybean meal basal diet with low PKM levels (5% and 7.5% in starter and grower diets, respectively) and 2) corn-soybean basal diet with high PKM levels (10% and 15% in starter and grower diets, respectively). The experiment was conducted from 1 to 35 days of age (DOA). All birds were raised in an evaporative cooling house with pellet feed and water provided ad libitum. During 1-17 DOA, feeding diets with different levels of PKM had no effect on broiler performance (p > 0.05). During 18-35 DOA, feeding high levels of PKM had no significant effect on body weight gain, feed intake and mortality of broilers. However, birds fed high PKM diets had a significantly higher feed conversion ratio (FCR) than the low PKM group (P = 0.0495). Throughout the experimental period (1-35 DOA), feeding high levels of PKM had no effect on bodyweight gain but feed intake tended to increase with high PKM levels (P = 0.0873). This led to a significant lower feed conversion ratio of broilers (P = 0.0505). No significant effect of PKM level was observed on the ileum morphology and litter quality of broilers. It was concluded that feeding high levels of PKM had a negative effect on the feed efficiency but not on the gut health and litter quality of broilers.